The myodocope ostracod Entomozoe from the early Silurian of Severnaya Zemlya, Russian Arctic - Siveter, D; Bogolepova, O (2006)
The myodocope ostracod Entomozoe aff. Entomozoe tuberosa (Jones 1861) has been identified from the Silurian Telychian Stage, Llandovery Series of Severnaya Zemlya, Russia. Entomozoe was previously known only from Scotland (E. tuberosa), Greenland (E. aff. E. tuberosa) and South China (E. cf. E. tuberosa). The new find signifies that Entomozoe has biostratigraphical and palaeogeographical significance: all occurrences are from Upper Llandovery sediments of tropical/subtropical palaeolatitudes. It represents a rare and early species link between the 'Baltic-British' Silurian ostracod faunal province and;'ostracod assemblages of the Russian Eurasian Arctic, and supports the notion that the North Kara Terrane and Laurentia were once palaeogeographically close. The palaeoenvironmental setting of the Russian material is consistent with the idea that this Early Silurian myodocope was probably benthonic.